The Different Effect between Brisk Walking Exercise and Qigong Exercise on Blood Pressure of the Elderly with Hypertension in Gajahan Health Center - Nabira, Hafifah Refi; Hartono, Hartono; Rifai, Akhmad (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2025)
Hypertension is the third leading cause of death in the world. Uncontrolled hypertension can affect the function of other organs. Efforts to control blood pressure including physical activity such as brisk walking exercise and qigong exercise. This study aims to identify the different of effect between brisk walking exercise and qigong exercise in lowering blood pressure of the elderly with hypertension. This is a research with quasy experiment design pre-posttest without control group. The sample 50 elderly with hypertension who was selected using purposive sampling, and divided into two intervention groups; each group totaling 25 respondents. The two groups were given brisk walking exercise and qigong exercise seven times in two weeks with an interval of days for every exercise. The results of paired t-test showed a p-value of 0.001 in the brisk walking exercise group and of 0.020 in the qigong (p-value <0.05). This means that the brisk walking exercise and qigong exercise, both have an effect on lowering blood pressure of the elderly with Hypertension in Gajahan Health Center. The results of the independent t-test in both groups for systolic and diastolic value are 0.894 and 0.357 respectively, meaning that there was no significant difference on the effect of the interventions in the two groups (p-value> 0.05). It can be concluded that there brisk walking exercise and qigong exercise are two kinds of exercise that can be implemented to lowering blood pressure among elderly with hypertension. There was no significant different on the effectiveness of the two exercise, thus, the elderly can choose one of the two exercises that suit their need the most.